PENERAPAN HYGIENE SANITASI PADA PRAKTEK TATA KECANTIKAN KULIT MAHASISWA AKS- AKK YOGYAKARTA - Enny Harwiyati (Jurnal Socia Akademika, 2022)
This study aims to provide understanding and knowledge on the application of sanitary hygiene in work fields related to skin beauty, including caring for facial skin, the body, and SPA caring for hands, feet, and nails. This research uses qualitative methods with a descriptive method approach. Data obtained by observation methods to collect data on the results of observations and assessments during skin beauty practices. Visual analysis to collect data focuses on the sterilization of tools, customer maintenance actions, and treatment methods used. Instruments prepared to achieve occupational safety standards, health, and safety in implementing skin beauty practices in the AKS AKK cosmetology study program students. So that the realization of a conducive, effective, and responsible climate will be achieved according to the recommendations of work standards in the beauty field. Furthermore, businesses in the Beauty and SPA as users of AKS - AKK Cosmetology Study Program graduates are guided by the Indonesian National Work Competency Standards (SKKNI), which refers to knowledge, skills, and mindset attitudes.